2006
DOI: 10.1128/jcm.00879-06
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Detection of Carbapenem-Susceptible Metallo-β-Lactamase-Producing Gram-Negative Bacilli in the Clinical Laboratory

Abstract: Rapid detection of metallo-␤-lactamase (MBL)-producing gram-negative pathogens is critical to prevent their widespread dissemination. Thus far, no standardized phenotypic method is available, and previously reported techniques have poor sensitivity for detecting carbapenem-susceptible MBL-carrying isolates, an increasingly described phenomenon. We developed a phenotypic detection method using both a double-disk synergy test and a combined-disk test with imipenem and 292 g EDTA on one agar plate. Genotypic conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
155
4
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(185 citation statements)
references
References 26 publications
6
155
4
10
Order By: Relevance
“…VIM was also predominant among 75 randomly selected A. baumannii isolates (65 % of which were carbapenem resistant), accounting for 96 % of the isolates. This confirms results of previous studies that showed that the number of isolates carrying a gene for the VIM-type enzyme is much higher than the number of isolates phenotypically resistant to carbapenems (Franklin et al, 2006;Peleg et al, 2005).…”
Section: A Baumanniisupporting
confidence: 81%
“…VIM was also predominant among 75 randomly selected A. baumannii isolates (65 % of which were carbapenem resistant), accounting for 96 % of the isolates. This confirms results of previous studies that showed that the number of isolates carrying a gene for the VIM-type enzyme is much higher than the number of isolates phenotypically resistant to carbapenems (Franklin et al, 2006;Peleg et al, 2005).…”
Section: A Baumanniisupporting
confidence: 81%
“…An increase in the diameter of the inhibition zone by ¢4 mm around the imipenem+EDTA, meropenem+EDTA and ertapenem+EDTA as compared to that of the imipenem, meropenem and ertapenem alone indicated the presence of MBL (Franklin et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…[3] Currently, no standardised method for MBL detection has been proposed and despite PCR being highly accurate and reliable, its accessibility is often limited to reference laboratories. [4] Several non molecular techniques have been studied, all taking advantage of the enzyme's zinc dependence by using chelating agents, such as EDTA or 2 mercaptopropionic acid, to inhibit its activity. [4] Our institute, a tertiary care centre in India, has a very high prevalence of nosocomial infections due to P. aeruginosa.…”
mentioning
confidence: 99%
“…[4] Several non molecular techniques have been studied, all taking advantage of the enzyme's zinc dependence by using chelating agents, such as EDTA or 2 mercaptopropionic acid, to inhibit its activity. [4] Our institute, a tertiary care centre in India, has a very high prevalence of nosocomial infections due to P. aeruginosa. [5,6] We have also found a very high prevalence of multidrug resistant (MDR) and ESBL positive gram negative bacteria in ICUs and other wards of our hospitals.…”
mentioning
confidence: 99%